Fiscal descentralization and big cities financing in Brazil - Fernando Rezende (Institute for Applied Economic Research (ipea), 2015)
Brazilian big cities have high needs but dispose of low means. This situation leads to a paradox: a higher dependence on the state and federal governments as compared with middle size and smaller cities with respect to the provision of urban and social services. Higher dependence means more submission to political alliances and less room for an effective social control on public spending. This paper explores some aspects of this particular situation, its main causes, and possible solutions.
Keywords: 330